190. Osteomyelitis Following Mandibular Reconstruction with Free Fibula Flap: A Cohort Study of an Emerging and Complex Bone and Joint Infection. (31st December 2020) - javaux, Clément; Daveau, Clémentine; Bettinger, Clothilde; Bourlet, jérôme; Dupieux-Chabert, Céline; craighero, Fabien; Fuchsmann, Carine; Céruse, Philippe; Sigaux, Nicolas; Ferry, Tristan; Valour, Florent
Abstract: Background: Free fibular flap (FFF) mandible reconstruction is at high risk of complications due to patient comorbidities, microvascular surgery after neck irradiation and intrabuccal exposure. We aimed to describe clinical and microbiological features, management and outcome of osteomyelitis following mandibular reconstruction with FFF. Methods: Patients referred to our reference center for an osteomyelitis following FFF reconstruction of the mandible were included in a retrospective cohort. Microbiology was described based on gold-standard samples. Risk factors for treatment failure (infection persistence or relapse, need for additional surgery for septic reason, infection-related death) were assessed by logistic regression and Kaplan-Meier survival curve analysis. Results: 48 patients (age, 60.5 [IQR, 52.4–66.6]; 30 males; 62.5%; modified Charlson comorbidity index, 4 [3–5]) were included. Indications for FFF mandible reconstruction were mostly carcinoma (n=27; 56.3%) and osteoradionecrosis (n=12; 25.0%), with 44 (82.9%) previous neck irradiation. FFF osteomyelitis were mostly early (≤ 3 months post-surgery; n=43; 89.6%). Main symptoms were local inflammation (n=28; 59.6%), ununion or sinus tract (n=28; 59.6%), bone or device exposure (n=21; 44.7%), and were associated with radiological signs for infection in 33 (75.0%) cases. Microbiological documentation highlighted Enterobacteriaceae (n=25; 61.0%), Streptococcus spp. (n=22; 53.7%), S. aureus (n=10; 24.4%), anaerobes (n=10, 24.4%), Enterococcus spp. (n=9; 22.0%) and non-fermenting Gram negative bacilli (GNB; n=8; 19.5%). Thirty-nine (81.3%) required surgery, consisting in debridement with implant retention in 25 (64.1%) cases, associated with a 93 (64–128) day course of antibiotherapy. After a follow-up of 18 (11–31) months, 24 (50.0%) treatment failure were observed. An early ID-specialist referral was the only significant predictor of favorable outcome (OR, 0.167; p =0.005). Non-fermenting GNB infections tended to be associated with a higher risk of failure (OR, 8.4; p =0.058). Probability of treatment failure of osteomyelitis following FFF mandible reconstruction according to ID-referral (A), CRP level 2 weeks after surgery (B) and presence of non-fermenting GNB Conclusion: Osteomyelitis following mandibular reconstruction with FFF represent difficult-to-treat infections. Our results advocate for a multidisciplinary management, including an early ID-specialist referral. Disclosures: All Authors : No reported disclosures